2016
DOI: 10.1111/myc.12452
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of posaconazole serum concentrations from haematological cancer patients on posaconazole tablet and oral suspension for treatment and prevention of invasive fungal infections

Abstract: Posaconazole tablet formulation (PTF) was developed to optimise bioavailability. This study compared posaconazole levels between patients on the PTF and oral suspension formulation (OSF). We also examined factors that may impact posaconazole levels. The primary and secondary objectives were analysed by comparing trough levels and attainment of target level between the formulation groups. For the 86 patients on PTF and 176 on OSF, the mean first levels was 1.32 μg ml (SD = 0.69) and 0.81 μg ml (SD = 0.59), P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
36
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 35 publications
(48 reference statements)
13
36
1
2
Order By: Relevance
“…The tablet and intravenous formulations were approved on the basis of safety and pharmacokinetic data, with corresponding phase III data for the tablet formulation recently being published (9). To date, several small, single-center studies have reviewed the initial implementation of PCZ tablets, focusing mainly on pharmacokinetic endpoints (5,6,(10)(11)(12). In agreement with our early experience, those reports also have shown that PCZ tablets yield higher serum concentrations than the suspension formulation and appear to be safe (5).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The tablet and intravenous formulations were approved on the basis of safety and pharmacokinetic data, with corresponding phase III data for the tablet formulation recently being published (9). To date, several small, single-center studies have reviewed the initial implementation of PCZ tablets, focusing mainly on pharmacokinetic endpoints (5,6,(10)(11)(12). In agreement with our early experience, those reports also have shown that PCZ tablets yield higher serum concentrations than the suspension formulation and appear to be safe (5).…”
supporting
confidence: 66%
“…The recently available intravenous (i.v.) and delayed-release (DR) tablet formulations of PCZ result in significantly higher serum PCZ concentrations and increased attainment of traditional pharmacokinetic targets, compared to the PCZ suspension (5,6). Additionally, the DR formulation has been demonstrated to provide more consistent absorption and is minimally affected by gastric pH and motility (7,8).…”
mentioning
confidence: 99%
“…39,40 The delayed release oral tablet is considered a more reliable option for the prophylaxis or treatment of IFIs. Studies have suggested that the posaconazole oral tablet has higher azole plasma levels 41 , better absorption 42 , and improved bioavailability 43 than that of oral suspension. Furthermore, an intravenous formulation of posaconazole was developed and FDA-approved in 2014 for patients who are unable to take oral medications.…”
Section: Second Generation Triazoles: Voriconazole and Posaconazolementioning
confidence: 99%
“…Frequently used for the prevention of fungal infections in high-risk populations, this agent is also useful during the treatment of multiple forms of aspergillosis (1). Recent studies have shown that the new posaconazole delayed-release tablets have superior bioavailability compared to the liquid suspension formulation (2,3). As higher serum posaconazole concentrations have been associated with improved clinical responses (4), this formulation has been a welcome addition to available treatment options.…”
mentioning
confidence: 99%